Effects of durian fruit on blood pressure of spontaneously hypertensive rats - Malina Jasamai,; Nurul Hanis Samsudin,; Norazrina Azmi,; Kumolosasi, Endang (Penerbit Universiti Kebangsaan Malaysia, 2018)
Durian or scientifically known as Durio zibethinus is one of the most well-known seasonal fruits in the Southeast Asia region. However, its safe consumption in individuals with hypertension is still controversial. This study was conducted to investigate the effect of durian on blood pressure of spontaneously hypertensive rat model. Four groups of rats (n=5) were fed with either a low dose durian (26 g/kg), a high dose durian (52 g/kg), sugar solution (8 mL/kg) which has similar sugar composition in the durian as placebo control, and distilled water as vehicle control (8 mL/kg) for 14 days. The durian doses for rats were obtained by converting from human doses. Baseline reading of blood pressure and heart rate were recorded before the first oral administration of durian. The blood pressure and heart rate were also measured 1 h after the durian oral administration on day 1, 3, 7 and 14 of the experiment. In conclusion, durian fruit possessed an acute effect on the blood pressure of hypertensive rats but heart rate was unaffected. High dose administration of durian led to significant elevation of blood pressure after 1 h of consumption. Meanwhile, low dose of durian (26 g/kg) caused an insignificant reduction in systolic and diastolic blood pressure. Tolerance to the durian fruit was observed after three to seven days of the oral administration and low dose consumption of durian fruit was safe in the hypertensive rat.